All about flooble | fun stuff | Get a free chatterbox | Free JavaScript | Avatars    
perplexus dot info

Home > Just Math
Time for T with U (Posted on 2014-01-19) Difficulty: 3 of 5

Start with the Chebyshev polynomials of the first kind, omitting even values:

T1(x)=x
T3(x)=4x3-3x
T5(x)=16x5-20x3+5x
T7(x)=64x7 -112x5 +56x3 -7x
....etc.

Change all minus signs to plusses, and replace each exponent, m, by (m-1)/2:

T1(x)=1
T3(x)=4x+3
T5(x)=16x2 +20x+5
T7(x)=64x3 +112x2 +56x+7
....etc., to produce (omitting (x) for clarity of exposition) the new polynomials, P1, P2, P3, P4...Pn.

Similarly, take the Chebyshev polynomials of the second kind, this time omitting odd values :

U0(x) = 1
U2(x) = (4x2 -1)
U4(x) = (16x4 -12x2 +1)
U6(x) = (64x6 -80x4 +24x2 -1)
....etc.

Change all minus signs to plusses, and replace each exponent, m, by (m/2):

U0(x) = 1
U2(x) = (4x+1)
U4(x) = (16x2 +12x+1)
U6(x) = (64x3 +80x2 +24x+1)
....etc., to produce (omitting (x) for clarity of exposition) the new polynomials, Q1, Q2, Q3, Q4...Qn.

Amazingly, (Pn)2 *x+1 = (Qn)2 *(x+1)

Prove it!

  Submitted by broll    
No Rating
Solution: (Hide)
I won't bore with theory, just work through the equivalences.

We start with:

P1=1
P2=4x+3
P3=16x^2+20x+5
P4=64x^3+112x^2+56x+7
...

Q1=1
Q2=4x+1
Q3=16x2+12x+1
Q4=64x3+80x2+24x+1
...

First, conduct the squaring operation to confirm the relation:

(4n+3)^2*n+1 = (n+1) (4n+1)^2
(16n^2+20n+5)^2*n+1 = (n+1) (16n^2+12n+1)^2
(64n^3+112n^2+56n+7)^2*n+1 = (n+1) (64n^3+80n^2+24n+1)^2
(256n^4+576n^3+432n^2+120n+9)^2*n+1 = (n+1)
(256n^4+448n^3+240n^2+40n+1)^2
...etc.

Note that all these equations are of the form k*a^2=(k-1)b^2+1, with n=k, a crucial point.

Second, cross-relate to the Chebyshev polynomials (just the P series to show the method)

ChebyshevTn(x):
T0(x)=1
T1(x)= x
T2(x)= 2x^2-1
T3(x)= 4x^3-3x
T4(x)= 8x^4-8x^2+1

ChebyshevUn(x)
U0(x)= 1
U1(x)= 2x
U2(x)= 4x^2-1
U3(x)= 8x^3-4x
U4(x)= 16x^4-12x^2+1

Given that P2=4x+3; let s be the smallest solution, greater than 1, that solves the corresponding Pell-like equation, with

s=T1[x]=(2x+1)=U1[x],
k=(x+1),
m=2;

where [x] denotes the base value before multiplication of T1(x) and U1(x); k(k-1) = D in the canonical equation a^2=Db^2+1; and m is the auxiliary multiplier corresponding to D (as it happens, m = 2 in such cases).

(4x+3) = (x+1)*2+(2x+1)
16x^2+20x+5 = (x+1)*((2x+1)*2)*2+2*(2x+1)^2-1
64x^3+112x^2+56x+7 = (x+1)* (4*(2x+1)^2-1)*2+4*(2x+1)
^3-3*(2x+1)
256x^4+576x^3+432x^2+120x+9 = (x+1)*(8*(2x+1)^3-4*(2x+1))*2+8*(2x+1)^4-8*(2x+1)^2+1
1024x^5+2816x^4+2816x^3+1232x^2+220x+11 = (x+1)*2*(16*(2x+1)^4-12*(2x+1)^2+1)+ 16*(2x+1)^5-20*(2x+1)^3+5*(2x+1)

etc.

In general: Pn[s] = 2*Un[s](x+1)+Tn[s], and we are done.

Comments: ( You must be logged in to post comments.)
  Subject Author Date
There are no comments yet.
Please log in:
Login:
Password:
Remember me:
Sign up! | Forgot password


Search:
Search body:
Forums (1)
Newest Problems
Random Problem
FAQ | About This Site
Site Statistics
New Comments (7)
Unsolved Problems
Top Rated Problems
This month's top
Most Commented On

Chatterbox:
Copyright © 2002 - 2024 by Animus Pactum Consulting. All rights reserved. Privacy Information